1996
DOI: 10.1149/1.1837200
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Chlorine in Selective Silicon Epitaxy by Chemical Vapor Deposition

Abstract: Si thermal etching studies have been performed using pure Cl2 in an ultrahigh vacuum rapid thermal chemical vapor deposition reactor in the temperature range of 650–850°C and the flow rate range of 1–10 sccm which corresponds to a pressure range of 0.5–3.5 mTorr. The effects of temperature and Cl2 flow were investigated with thermodynamic equilibrium calculations performed to determine possible reaction pathways. The effect of adding H2 , up to 500 sccm, on Si etch rates at 800 and 850°C was also obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Due to the higher Si 1 À x Ge x -etching capacity for 5-sccm Cl 2 than 1-sccm Cl 2 , the growth rate of Si 1 À x Ge x SEG with 5-sccm Cl 2 is lower than that with 1-sccm Cl 2 . Surface passivation of Si 1 À x Ge x films with chlorine during the Cl 2 exposure step might be responsible for the longer incubation time of Si 1 À x Ge x SEG with addition of Cl 2 [7,12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the higher Si 1 À x Ge x -etching capacity for 5-sccm Cl 2 than 1-sccm Cl 2 , the growth rate of Si 1 À x Ge x SEG with 5-sccm Cl 2 is lower than that with 1-sccm Cl 2 . Surface passivation of Si 1 À x Ge x films with chlorine during the Cl 2 exposure step might be responsible for the longer incubation time of Si 1 À x Ge x SEG with addition of Cl 2 [7,12].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, by dint of separate injection of Cl 2 and source gas of Si 2 H 6 and GeH 4 , the chances for generation of Si chlorides and chlorosilanes and the corresponding Ge species can be ruled out, and their effect on our Si 1 À x Ge x SEG can be excluded. When the surface of S 1 À x Ge x film grown on Si(0 0 1) surface is exposed to Cl 2 gas, two desorption species, GeCl 2 and SiCl 2 , can be mostly generated [12,16]. Decrease in the Ge concentration in our Si 1 À x Ge x SEG films by addition of Cl 2 can be attributed to the discrepancy between desorption energy of GeCl 2 in the Cl 2 / Ge(0 0 1) system, i.e., 25.6 kcal/mol and SiCl 2 in the Cl 2 /Si(0 0 1) system, i.e., 73.0 kcal/mol [17,18].…”
Section: Resultsmentioning
confidence: 99%
“…However, the etch rates using this process are very low below 800 o C. For temperatures less than 750 o C, the etch rates with HCl have been observed to be less than 1nm/min (3). Previously attempts made to use using chlorine instead of hydrogen chloride to etch silicon in a hydrogen ambient (4). It was observed that the etch rate was still negligible below 750 o C. The authors believed that hydrogen was reacting with the chlorine to form HCl.…”
Section: Chlorine Thermal Etchingmentioning
confidence: 99%
“…However, the SEG-Si surface was uneven, which the highest value (R max ) of the surface roughness was 5.5 nm in the area of 4 Â 4 mm 2 by atomic force microscopy (AFM) measurement. It appeared that the Si 2 H 6 dissociation vaporized from the substrate surface by reacting with Cl 2 dissociation [14]. Therefore, the deoxidation effect of Si 2 H 6 dissociation must be reduced and the resulting SEG-Si surface was rough.…”
Section: Optimization Of the Process Conditions Of Segsi Growthmentioning
confidence: 99%